Iowa Birdline update, May 21, 1990 - Fuller, Charleset al; Iowa Ornithologists' Unionet al (1990)
Summary for the Iowa Birdline update for May 21, 1990. Highlights of the update include the continued presence of a Prairie Warbler and a Henslow's Sparrow. Also of note were sightings of 48 Red-necked Phalaropes, numerous reports of Cattle Egrets, and a brief appearance of a Black-headed Grosbeak. In addition, several species of shorebirds and Ducks were also observed. Epson - sheet feed/flatbed